A non-classical PUF family protein in oomycetes functions as a pre-rRNA processing regulator and a target for RNAi-based disease control. - Hui Feng; Tianli Liu; Chuanxu Wan; Zhichao Zhang; Yuanchao Wang; Xiaobo Zheng; Jie Wang; Wenwu Ye (PLoS Pathogens)
Ribosome biogenesis is an essential and tightly regulated process linked to cell proliferation and growth. However, its regulatory mechanisms in oomycetes, a group of organisms with significant agricultural and ecological importance, remain unclear. In this study, we identify Puf4, a non-classical PUF (Pumilio and FBF) family RNA-binding protein that plays a conserved and crucial role in pre-rRNA processing in oomycetes. Knockout of PuPuf4 in Pythium ultimum or its ortholog PsPuf4 in Phytophthora sojae results in defective vegetative growth, impaired development, and reduced pathogenicity. Specifically, PuPuf4 binds to the H68 component of 25S rRNA, and its knockout leads to overaccumulation of rRNA processing intermediates, including 5'ETS, ITS1, and ITS2 precursors. Additionally, the AG-rich motif identified as the first binding motif of L-shaped PUF proteins, including PuPuf4, APUM24, and ScPuf6, may contribute to their specific RNA-binding affinity due to its unique structural features. Given the conserved role of Puf4 in oomycete pathogenicity, we developed the first nano-material-free dsRNA delivery system via zoospore-specific uptake, effectively attenuating virulence in Pythium aphanidermatum and Ph. sojae through RNAi targeting Puf4. This study presents novel findings on structural and functional conservation of Puf4 and offers a promising RNAi-based strategy for controlling oomycete plant diseases.